Morphology and protein adsorption of aluminum phosphate and aluminum hydroxide and their potential catalytic function in the synthesis of polymeric emulsifiers - Cheng, Yu-Jhen (Colloids and surfaces. A, Physicochemical and engineering aspects, 2021)
© 2020 Elsevier B.V. All rights reserved.